Small Molecule Cjoc42 Improves Chemo-Sensitivity and Increases Levels of Tumor Suppressor Proteins in Hepatoblastoma Cells and in Mice by Inhibiting Oncogene Gankyrin - D’Souza, Amber M.; Cast, Ashley; Kumbaji, Meenasri; Rivas, Maria; Gulati, Ruhi; Johnston, Michael; Smithrud, David; Geller, James; Timchenko, Nikolai (Frontiers in Pharmacology, 2021)
Objective: Relapsed hepatoblastoma (HBL) and upfront hepatocellular carcinoma (HCC) are notoriously chemo-resistant tumors associated with poor outcomes. Gankyrin (Gank) is a known oncogene that is overexpressed in pediatric liver cancer and implicated in chemo-resistance. The goal of this study was to evaluate if the Gank-tumor suppressor axis is activated in chemo-resistant hepatoblastoma patients and examine if an inhibitor of Gank, Cjoc42, might improve the chemosensitivity of cancer cells. Methods: Expression of Gank and its downstream targets were examined in fresh human HBL samples using immunostaining, QRT-PCR, and Western Blot. Cancer cells, Huh6 (human HBL) and Hepa1c1c7 (mouse HCC) were treated with Cjoc42 and with Cjoc42 in combination with cisplatin or doxorubicin. Cell proliferation, apoptosis, and chemo-resistance were examined. To examine activities of Cjoc42 in vivo, mice were treated with different doses of Cjoc42, and biological activities of Gank and cytotoxicity of Cjoc42 were tested. Results: Elevation of Gank and Gank-mediated elimination of TSPs are observed in patients with minimal necrosis after chemotherapy and relapsed disease. The treatment of cancer cells Huh6 and Hepa1c1c7 with Cjoc42 was not cytotoxic but lead to reduced proliferation instead. In combination with cisplatin or doxorubicin, Cjoc42 caused a significant increase in cytotoxicity compared to chemotherapy alone which is accompanied with increased apoptosis. Examination of Cjoc42 in WT mice showed that Cjoc42 is well tolerated and does not show toxicity, but increases levels of tumor suppressors CUGBP1, Rb, p53, C/EBPα, and HNF4α by blocking their Gank-dependent degradation. Conclusions: Our work shows that Cjoc42 might be a promising adjunct to chemotherapy for the treatment of severe pediatric liver cancer and presents mechanisms by which Cjoc42 increases chemo-sensitivity.